1997
DOI: 10.1007/s004010050752
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase-, N -methyl- d -aspartate receptor-, glutamate- and aspartate-immunoreactive neurons in the mouse arcuate nucleus: effects of neonatal treatment with monosodium glutamate

Abstract: Glutamate-, aspartate-, N-methyl-D-aspartate receptor (NMDAR1 and 2 subunits)-, and nitric oxide synthase (NOS)-immunoreactive neurons were studied in the arcuate nucleus (AN) of mice treated neonatally with monosodium glutamate (MSG) which is known to cause extensive neuronal loss in this hypothalamic nucleus. It was found that intensely stained glutamate- and aspartate-immunoreactive neurons present in the AN of control mice were completely absent in the MSG-lesioned AN as well as the ventromedial nucleus la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The present data showed that in the arcuate nucleus from control animals both neuronal and glial cells conformed to standard descriptions 19,20,26 . By contrast, in NMA‐treated rats, LM showed a typical marked cell depletion; furthermore, degenerated cells were identified by their pyknotic nuclei and edematous swelling of the surrounding cytoplasmic compartment giving the typical appearance of a “bull's eye.” These findings are in agreement with previous studies that reported cell loss and the appearance of degenerated neurons in the arcuate nucleus of rats and mice after NMDA receptor agonist administration 18–21 . At ultrastructural level, NMA induced several alterations including chromatin margination, nuclear shrinkage, mitochondria with matrix dilution, dilated endoplasmic cisternae, and electron dense cytoplasm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data showed that in the arcuate nucleus from control animals both neuronal and glial cells conformed to standard descriptions 19,20,26 . By contrast, in NMA‐treated rats, LM showed a typical marked cell depletion; furthermore, degenerated cells were identified by their pyknotic nuclei and edematous swelling of the surrounding cytoplasmic compartment giving the typical appearance of a “bull's eye.” These findings are in agreement with previous studies that reported cell loss and the appearance of degenerated neurons in the arcuate nucleus of rats and mice after NMDA receptor agonist administration 18–21 . At ultrastructural level, NMA induced several alterations including chromatin margination, nuclear shrinkage, mitochondria with matrix dilution, dilated endoplasmic cisternae, and electron dense cytoplasm.…”
Section: Discussionsupporting
confidence: 93%
“…Since it can be easily administered and rapidly enters the brain, xenon may be regarded as a good candidate for neuroprotectant agent. The hypothalamic region, including the arcuate nucleus–median eminence complex, has been frequently used in studies dealing with glutamate neurotoxicity 19–23 . Indeed, this area appears the most glutamatesensitive among the circumventricular organs where the fenestrated endothelium allows free access to amino acids present in circulating blood.…”
Section: Introductionmentioning
confidence: 99%
“…Administering Glu to newborn rodents at 2-4 mg/g BW results in complete destruction of the arcuate nucleus (AN) neurons 9 , and damages a number of other hypothalamic nuclei. Transporter proteins guarantee removal of Glu from the extracellular fluid and long-term maintenance of low and non-toxic concentrations in the central nervous system (CNS).…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…The N-methyl-D-aspartate receptor (NMDA-R) is fully functional in the rat early in embryogenesis. Xue et al (1997) found that GLU-and aspartate-immunoreactive neurones were completely absent in the monosodium glutamate (MSG)-lesioned arcuate nucleus as well as the ventromedial nucleus lateral to the arcuate nucleus, in mice treated neonatally with MSG. Similarly, NMDA-R1-immunoreactive neurones were mostly absent in the MSG-lesioned arcuate nucleus but remained intact in the ventromedial nucleus.…”
Section: Introductionmentioning
confidence: 99%